A 140-kilodalton extracellular protein is essential for the accumulation of Staphylococcus epidermidis strains on surfaces. - Hussain, M (1997)
Two distinct pathogenic mechanisms, adhesion to polymer surfaces and subsequent accumulation of sessile bacterial cells, are considered important pathogenic steps in foreign body infections caused by Staphylococcus epidermidis. By using mitomycin mutagenesis, we have recently generated a mutant, strain M7, from S. epidermidis RP62A which is unaffected in adhesion but deficient in accumulation on glass or polystyrene surfaces and lacks a 115-kDa extracellular protein (designated the 140-kDa antigen; F. Schumacher-Perdreau, C. Heilmann, G. Peters, F. Götz, and G. Pulverer, FEMS Microbiol. Lett. 117:71-78, 1994). To evaluate the role of this protein in accumulation, we harvested extracellular proteins from S. epidermidis RP62A grown on dialysis membranes placed over chemically defined medium, purified the protein by using ion-exchange chromatography, determined its N-terminal amino acid sequence, and raised antiserum in rabbits. The antibody recognized only a single band in a Western immunoblot of the crude extracellular extract. With the microtiter biofilm test, antiserum at a dilution of < or =1:1,000 blocked accumulation of RP62A up to 98% whereas preimmune serum did not. The 140-kDa antigen was found only in extracellular products from bacteria grown under sessile conditions. Of 58 coagulase-negative clinical isolates, 32 strains were 140-kDa antigen positive and produced significantly larger amounts of biofilm than the 26 strains that were 140-kDa antigen negative. The 140-kDa protein appears to be biochemically and functionally unrelated to any previously described factors associated with biofilm formation. Thus, the 140-kDa antigen, referred to as accumulation-associated protein, may be a factor essential in S. epidermidis accumulation and, due to its immunogenicity, may allow the development of novel immunotherapeutic strategies for prevention of foreign body infection.